Dialogue with the Other: The Inter-religious Dialogue - Tom, Mari (Journal of Dharma, 1992)
David Tracy, Dialogue with the Other: The Inter-religious Dialogue, Michigan : William B. Eerdmans Publishing Co., 1990, pp. xii + 124, $12.45